The Importance of Sustainable Development And The Benefits of Renewable Energy - Tvauri, Giga (European Scientific Journal, ESJ, 2023)
Global warming, climate change, and excess carbon emissions are the issues that serve as the main challenges of the modern and civilized world. In September 2015, world leaders unanimously adopted Sustainable Development Goals which governments began to implement step by step. In 2017, Georgia made 17 goals of sustainable development a national priority. The development of renewable energies is in line with several goals of sustainable development. It is directly related to the 7th goal. Universal access to affordable, reliable, stable, and modern energy is reflected in economic, ecological, and social aspects. At the same time, the energy sector ranks second in carbon emissions. Therefore, harnessing and developing renewable energies is the best way to deal with climate change. The purpose of the paper is to study the importance of renewable energies and sustainable technologies for the country’s economy and how sustainability affects the environment and society. The research includes the implementation of sustainable technologies and their impact, both on a specific entity and the country’s long-term economic perspective.